The Concept of Ideological Distance : A Case Study of the Diplomatic Crisis between Spain and Argentina in 2024 - Kepková, Natálie; Lehmannová, Zuzana, 1951-; Hennlichová, Marcela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the role of ideology in the diplomatic crisis between Spain and Argentina in 2024 and seeks to identify the ideological dimension of the genesis of this crisis. The basic supposition with which the thesis operates is the assumption of the different ideological affiliations of the two protagonists of the crisis, namely the Prime Minister of Spain, Pedro Sánchez, who is traditionally perceived as a strong supporter of socialism, and Javier Milei, the newly elected President of Argentina, whose political inclination is strongly right-wing and who tends towards anarcho-capitalism on economic issues. The dimensions of their ideological distance and the impact of this fact are considered in the context of Ideological Distance Theory, formulated by M. L. Haas, which examines the influence of leaders' ideology on countries' bilateral relations. The aim of the thesis is to answer the research questions "In what ways did ideology contribute to the crisis, what ideological factors are behind its escalation and what role did Ideological Distance Theory play in the crisis". For these purposes, a qualitative textual analysis method was applied to transcriptions of speeches by statesmen to reveal how they express themselves on issues having an ideological dimension. By interpreting the findings from the analysis and evaluating them in the context of the crisis and the history of bilateral relations between the two countries, which is part of the case study, it was found that the role of ideology in the crisis was crucial. The different perspectives of statesmen on both sides, conditioned by ideology, lead to very different world views and political priorities at the theoretical level, while at the practical level their different views make cooperation impossible.
At the same time, the validity of the Ideological Distance Theory was confirmed for this case, opening up the possibility of its universal validity and creating a topic for a possible further research.
Vedoucí práce: Zuzana Lehmannová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses